Enhancing Writing Literacy Teachers’ through AI Development - Fitri Wulandari; Missy Tri Astuti; Marhamah Marhamah (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The rapid evolution of technological tools, particularly Artificial Intelligence (AI), has resulted in the integration of technology-aided learning resources within educational environments. This study focuses on teachers' utilization of AI and technology tools in the context of English academic writing and its impact on their writing literacy. This research employs a qualitative approach, gathering data through questionnaires involving 20 English teachers from junior high schools. The findings highlight that these tools encourage and facilitate the enhancement of writing skills among teachers. Participants indicated using tools such as Grammarly, Quill Bot, ChatGPT, Mendeley, and Turnitin, which offer direct feedback, corrections, and aid in writing skills development. Specifically, the participants reported that these tools contribute to their comprehension of grammatical rules and vocabulary acquisition. Moreover, they found these tools instrumental in crafting more cohesive and coherent writing. This study suggests that integrating technology tools into English academic writing has the potential to transform the development and assessment of writing abilities. Nonetheless, it remains crucial for teachers to strike a balance between utilizing these tools and nurturing their writing skills to ensure ongoing writing enhancement